KRIMINALISASI KPK SUATU TINJAUAN HUBUNGAN ANTARA FAKTA, NORMA, MORAL, DAN DOKTRIN HUKUM DALAM PERTIMBANGAN PUTUSAN HAKIM - Kamri Ahmad (Masalah-Masalah Hukum, 2011)
"The notion of justice without law seems preposterous, if not terrifying", in his book 'Justice Without Law' (1983) by Jerold S. Auerbach. Its the same as if Indonesia recognized that "it's constitutional state', but justice of law disregarded. But actually if we are talking about justice, so is there a law, as Cicero said "Ubi societas, ibi ius" 'where there is society. so there is a law'. In this article would be explaind about corelation between the crimina-lization and facts. norm. moral, and doctrin of law in judges made law consideration.